Answer:
.022
Step-by-step explanation:
Answer on Khan
solving equation in terms of x we get ![x=-9-3y](https://tex.z-dn.net/?f=x%3D-9-3y)
solving equation in terms of y we get ![y=-3-1/3x](https://tex.z-dn.net/?f=y%3D-3-1%2F3x)
Step-by-step explanation:
We need to solve the equation: ![-2(x + 3y) = 18](https://tex.z-dn.net/?f=-2%28x%20%2B%203y%29%20%3D%2018)
Solving the equation:
![-2(x + 3y) = 18\\-2x-6y=18](https://tex.z-dn.net/?f=-2%28x%20%2B%203y%29%20%3D%2018%5C%5C-2x-6y%3D18)
Simplifying and finding value of x:
![-2x-6y=18\\-2x=18+6y\\-2x/-2=18/-2+6y/-2\\x=-9-3y](https://tex.z-dn.net/?f=-2x-6y%3D18%5C%5C-2x%3D18%2B6y%5C%5C-2x%2F-2%3D18%2F-2%2B6y%2F-2%5C%5Cx%3D-9-3y)
We can simplify and find value of y as well:
![-2x-6y=18\\-6y=18+2x\\-6y/-6=18/-6+2x/-6\\y=-3-1/3x](https://tex.z-dn.net/?f=-2x-6y%3D18%5C%5C-6y%3D18%2B2x%5C%5C-6y%2F-6%3D18%2F-6%2B2x%2F-6%5C%5Cy%3D-3-1%2F3x)
So, solving equation in terms of x we get ![x=-9-3y](https://tex.z-dn.net/?f=x%3D-9-3y)
solving equation in terms of y we get ![y=-3-1/3x](https://tex.z-dn.net/?f=y%3D-3-1%2F3x)
Keywords: Solving Equations
Learn more about Solving Equations at:
#learnwithBrainly
《ANSWER》
《LINEAR EQUATIONS》
Solving all we get as
↪1) 5 (x -2) = 5x - 7
since after solving X is cancelled , NO SOLUTION
↪2) -3 (x - 4) = -3x + 12
SINCE after solving X is any value , infinitely many solutions
↪3) 4 (x + 1) = 3x + 4
solving we get as , 4x+ 4 = 3x + 4 =》 X =0
only one solution
↪4) -2 (x-3) = 2x - 6
Only one solution
↪5) 6 (x + 5) = 6x + 11
NO SOLUTION
All the equations are solved by the distributive law of algebra
I believe it’s 5,193.0315 I’m not to sure
I’m not 100% certain but i’m pretty sure 1:3 works